The Mismatch Between Macroeconomic Stability and Declining Stock Performance of Digital Banks in Indonesia: An Empirical Study of 2022-2023 - Arif, Muhammad; Sovia, Annida Karima (UIN Syekh Ali Hasan Ahmad Addary Padangsidimpuan, 2024)
This study examines the mismatch between macroeconomic stability and the stock performance of digital banks in Indonesia over the period 2022-2023. The results of the analysis show that the USD/IDR exchange rate and Bank Indonesia interest rate have a significant negative effect on stock prices, while inflation shows no significant effect. These findings suggest that despite stable macroeconomic conditions, the share prices of digital banks experienced a significant decline, indicating market inefficiencies. This study makes a theoretical contribution by revealing the role of exchange rate and interest rate fluctuations in influencing the stock performance of digital banks in emerging markets. In conclusion, factors such as investor sentiment, market behavior, and the influence of digital financial technology need to be taken into account in developing strategies to support the stability and growth of the digital banking sector in Indonesia. The results of this study are important for policymakers, regulators, and market participants in dealing with the challenges faced by the digital banking sector in Indonesia. Keywords Digital banking, macroeconomic stability, stock performance, market inefficiency.